2015
DOI: 10.17706/ijeeee.2015.5.2.62-72
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Creating, Sharing and Using Open Education Resources (OERs) in Universiti Sains Malaysia (USM)

Abstract: One of the emerging issues in educational discourse today is the development of Open Educational Resources (OERs) and its potential in expanding access and improving the quality of education, particularly in developing countries such as Malaysia. There are an increasing number of OER materials which are created and made available by multilateral agencies, consortia and individual organizations but it is under-utilized. The increasing potential of OER is said to bring change perspectives from learners as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
8
Order By: Relevance
“…Adoption of OER materials is claimed to contribute knowledge production and dissemination which in turn contributes to social equity, economic and social development and democracy (Shrivastava & Shrivastava, 2014). Research studies have suggested that educators' perceptions shape whether or not to adopt OER materials (Ganapathy, Wei, & Jong, 2015). Yet, the awareness of OER is not sufficient for educators to include OER in their teaching process, and the educational administration and institutional policies play significant roles in OER adoption (Sutton & Chadwell, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Adoption of OER materials is claimed to contribute knowledge production and dissemination which in turn contributes to social equity, economic and social development and democracy (Shrivastava & Shrivastava, 2014). Research studies have suggested that educators' perceptions shape whether or not to adopt OER materials (Ganapathy, Wei, & Jong, 2015). Yet, the awareness of OER is not sufficient for educators to include OER in their teaching process, and the educational administration and institutional policies play significant roles in OER adoption (Sutton & Chadwell, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Sin embargo, en los países africanos y en una buena parte de los países latinoamericanos y asiáticos, se identificaron como principales retos los problemas de infraestructura tecnológica y conexión a Internet. Una de las barreras más frecuentemente mencionada, es la poca claridad de los académicos con respecto a los derechos de autor [6], [13], [24], [25] así como pocos incentivos institucionales para que los académicos asuman las labores adicionales de desarrollar y refinar contenidos abiertos [2], [26], [27]. La falta de un canal central para compartir los recursos dentro de una institución es otro factor que desalienta una mayor participación de los académicos [6], [12], [27].…”
Section: Barrerasunclassified
“…En [24] los autores realizaron un estudio con 35 académicos de una universidad de Malasia. Los resultados son muy similares a los de [6], [13] en términos de la apertura a compartir con colegas cercanos y en la preocupación sobre los derechos de autor, sin embargo ellos detectaron mayor reticencia en los académicos a que los recursos creados por ellos puedan ser modificados por otras personas.…”
Section: Estudios Similaresunclassified
See 2 more Smart Citations